Anti-Caste Movements, Resistance, and Caste: An Introduction - Abraham, Janaki; Janarthanan, Dhivya (Social Change, 2024)
In his short story 'New Custom' (Naya Kaayda), Ajay Navaria (2013) describes how a tea-seller in a village asks a man, whom he had initially mistaken to be a Thakur, to wash the glass he had just drunk tea in. The protagonist of the story had come to the village to attend a wedding. His tall build and impeccable clothing lead the tea-seller to welcome him and coax him into having tea at his stall. But when he discovers that the person is in the village to attend a wedding in the house of a dalit man-and is by inference, dalit himself-he turns cold and rude and instructs him to wash his glass. The protagonist of the story refuses to do this. He asks 'why,' even as he remembers his father saying that class cannot mask caste differences. The tea-seller and many of the people gathered around insist that this is 'the custom of the village,' and urge him to wash the glass lest he gets beaten up. In the end, he buys the glass and smashes it to the ground, instead of washing it. Navaria describes how the tea-seller has a smile on his face, but the people gathered around them watch intently. A naked man who had been lying on the ground some distance away, apparently dead, suddenly sits up when the glass is smashed. He seems to register, more dramatically than others present, the impact of this act of resistance-a demand for new customs.
Keywords: Anti-Caste Movements; Dalit-Bahujan; Protagonist; Caste